Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
on a graph here is the answer
Step-by-step explanation:
![View image lucasrosales04](https://us-static.z-dn.net/files/d0a/13c0b1bf57d7ba0ad531783214f2afc0.gif)
Answer:
(0, 3 )
Step-by-step explanation:
Given the 2 equations
- x - 6y = - 18 → (1)
- 8x + y = 3 → (2)
Multiplying (2) by 6 and adding to (1) will eliminate the y- term
- 48x + 6y = 18 → (3)
Add (1) and (3) term by term to eliminate y , that is
- 49x + 0 = 0
- 49x = 0 , thus
x = 0
Substitute x = 0 into either of the 2 equations and solve for y
Substituting into (2)
- 8(0) + y = 3
y = 3
solution is (0, 3 )
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.